Ambient Inkjet‐Printed High‐Efficiency Perovskite Solar Cells: Manipulating the Spreading and Crystallization Behaviors of Picoliter Perovskite Droplets. Issue 5 (18th March 2021) - Zhang, Lihua; Chen, Shi; Wang, Xingzhu; Wang, Deng; Li, Yan; Ai, Qian; Sun, Xiyu; Chen, Jiabang; Li, Yang; Jiang, Xiongzhuo; Yang, Shihe; Xu, Baomin
Abstract : Drop‐on‐demand inkjet‐printing has the advantages of high cost‐effectiveness and powerful patterning ability, which can be a promising technique for perovskite pattern deposition. However, by far most of the reported works using inkjet‐printing for perovskite films fabrication are printing solvent‐rich wet precursor layers on the high‐temperature meso‐TiO2 substrate, and subsequently require a vacuum‐assisted thermal annealing process to enhance the crystallization of perovskite precursor, which largely elevates fabrication cost and process complexity. Herein, a heat‐assisted inkjet‐printing process is developed to directly print compact and uniform crystalline perovskite films on the planar PEDOT:PSS substrate under ambient condition. The effects of precursor composition, printing temperature, solvent system, and, especially, the printing parameters on the final morphology and microstructure of the printed perovskite films are systematically studied for the first time and the related crystal growth models are revealed, which provide a constructive guidance for the future studies on ambient inkjet‐printed perovskite films and devices. Based on these studies, a champion power conversion efficiency (PCE) of 16.6% for the ambient printed PSC devices is achieved. This work provides a reliable and cost‐effective approach for the scalable fabrication of perovskite films with a low material consumption. Abstract : Drop‐on‐demand inkjet‐printing has the advantages of high cost‐effectiveness and powerful patterning ability. In this work, a simple inkjet‐printing method is developed to prepare perovskite films under ambient condition, where the effects of precursor ink, substate conditions, and printing parameters on the morphology and microstructure of the printed perovskite films have been systematically investigated.